The narrows : [compact disc, unabridged] : a novel - Connelly, Michael, 1956- (Connelly, Michael, 1956- Harry Bosch series., 2004)
Weaving lines of poetry into his gruesome crimes, the serial killer known to millions as the Poet returns. Rachel Walling, the FBI agent who years earlier had tried to track him down, has not forgotten him, and neither has former LAPD detective Harry Bosch who receives a call from an old friend whose husband had recently died. Even though his death appeared natural, the man's ties to the hunt for the Poet make Harry look twice, inevitably placing him in the path of the most ruthless and ingenious murderer in Los Angeles' history.